Template Assisted Generation of Chiral Luminescence in Organic Fluorophores - Maniappan, Sonia; Jadhav, Ashok Badrinarayan; Kumar, Jatish (Frontiers in Chemistry, 2021)
Development of efficient ways of fabricating chiral light emitting materials is an active area of research due to the vast potential offered by these materials in the field of optoelectronic devices, data storage and asymmetric synthesis. Among the various methods employed, template assisted generation of chiral luminescence is gaining enormous attention due to its simplicity, applicability over a wide range of fluorescent molecules/dyes and the display of high anisotropic values.